Religiosity and Purchase Intentions of Halal Food : A Systematic Literature Review - Qumil Laila Arham; Winda Wulansari; Diatul Fajri; Farid Ahmad Marlion; Muhammad Anshari (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
The purpose of this study is to identify and analyze some of the main references related religiosity and purchase intention on halal food products. This research is a bibliometric analysis of systematic literature using VOSviewer with a scientific citation index derived from Science Direct. Based on several phases of systematic review methods, this study obtained 20 important references from the indicated journals ranging from 2020 to 2025. The study also examined the journals involved as well as the number of citations from contributing authors and countries. This study found that the Heliyon journal is the journal that discusses the most about purchase intention in halal food products. In terms of authors, the highest number of citations belongs to Naem Akhtar. This shows that his contribution to academic implementation is quite large. As for the country of origin of researchers, China is the most dominant country of origin of researchers followed by other Asian countries in the top position. Thus, there are opportunities for further research in halal food purchase intention. This research contributes to future research and has greatly contributed to answering research questions and answering questions of religion and consumer intentions